Phyllostachys Pubescens: From Traditional to Functional Food: Phyllostachys pubescens as functional food. Issue 3 (3rd April 2023) - Curci, Francesca; Cavalluzzi, M. M.; Milani, G.; Clodoveo, M. L.; Radojčić Redovniković, I.; Cellamare, S.; Franchini, C.; Mandracchia, D.; Corbo, F.
ABSTRACT: Bamboo shoot ( Phyllostachys pubescens ) is mainly cultivated in China and Japan. It represents a reservoir of micro and macronutrients and contains a high amount of proteins, essential amino acids, phenolic acids, sterols, and fibers. Thank to these compounds, several beneficial health effects have been attributed to the bamboo shoot. This review is aimed at discussing a collection of research papers on Bamboo shoot in pharmaceutical and food fields. A particular focus is addressed to the chemical profile, the different biological activities, the different uses, the traditional recipes, the methods of conservation and the treatments of the shoot. To the best of our knowledge, this is the first example of a comprehensive review that is focused exclusively on the applications of the shoot of bamboo Phyllostachys pubescens in different fields.